2015
DOI: 10.1159/000443616
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness and Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a major public health concern due to the high prevalence of associated cardiovascular (CV) disease. CV mortality is 10-30 times higher in end-stage renal disease patients than in the age-adjusted general population. The last 20 years have been marked by a huge effort in the characterization of the vascular remodeling process associated with CKD and its consequences on the renal, CV and general prognosis. By comparison with patients with normal renal function, with or without hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 72 publications
(98 reference statements)
1
34
1
2
Order By: Relevance
“…Kidney transplantations improve patient CV prognosis, but its impact on arterial stiffness is still controversial. Donor age, living kidney donation and mean blood pressure appear to be the main determinants of improvement in aortic stiffness after kidney transplantation 54 .…”
Section: Microvascular Complicationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Kidney transplantations improve patient CV prognosis, but its impact on arterial stiffness is still controversial. Donor age, living kidney donation and mean blood pressure appear to be the main determinants of improvement in aortic stiffness after kidney transplantation 54 .…”
Section: Microvascular Complicationsmentioning
confidence: 97%
“…Carotid-femoral PWV measurements improve the prediction of CV risk in CKD patients beyond the traditional and renal CV risk factors. However, conflicting results were published about the relationship between aortic stiffness and estimated glomerular filtration rate (eGFR) within the CKD population 54 . A recent meta-analysis of the usefulness of central pressure measurements for predicting CV disease events concluded that the augmentation index provided independent CV diseases predictive utility when modelled together with traditional blood pressure 17 .…”
Section: Microvascular Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…14a), as the number of identified renal prognostic factors was less for this subcohort. Recently, PP was found to be associated with CKD progression for all CKD stages [53]. In a review by Safar [54], PP × HR was said to be significant, in that HR has more substantial links with PP than with mean blood pressure; an increase in PP × HR, more than PP itself, might cause vascular wall fatigue, particularly in the presence of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…[2,4] Diabetic kidney disease (DKD) is defined as functional, structural and clinical alterations of the kidneys caused by diabetes. [5] Vitamin C, also, known as ascorbic acid and ascorbate, is a basic compound that belongs to the group of water-soluble vitamins. [6] Vitamin C can be produced by most animals and plants from Dglucose and D-galactose, whereas it is not produced in humans due to the lack of L-gulonolactone oxidase enzyme; and therefore, it should be taken externally.…”
Section: Introductionmentioning
confidence: 99%